(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article analyzes the formation, stages of development, and educational significance of mnemonic techniques, with particular emphasis on their application in teaching history. The role of mnemonics in memory development, their impact on effective retention of historical information, and their contribution to enhancing students’ analytical and critical thinking skills are examined. In addition, the main mnemonic methods used in learning foreign languages and memorizing historical facts are described.